PREVALENCE AND FACTORS ASSOCIATED WITH PROBABLE GENERALIZED ANXIETY DISORDER AMONG HEALTHCARE WORKERS WORKING IN MEDICAL LABORATORIES OF THE CENTRAL PENINSULAR MALAYSIA DURING COVID-19 PANDEMIC - Shawaluddin, Noor Syaqilah; Awaluddin, S Maria; Mahjom, Maznieda; Lim, Kuang Kuay; Tuan Lah, Tuan Mohd Amin; Kassim, Mohd Shaiful Azlan; Ghazali, Mizanurfakhri; Mat Lazim , Rosmanajihah; Ismail, Rohaida; Arip, Masita (Malaysian Journal of Public Health Medicine, 2023)
Mental health problems are major public health concerns during the COVID-19 pandemic due to uncertainties of the disease, public fears and movement control orders which interrupt economic activities. Uncertainties about the diseases could trigger anxiety, particularly among healthcare workers (HCWs) who are directly involved in handling COVID-19 patients and specimens. This study aims to determine the prevalence and factors associated with a probable generalized anxiety disorder (GAD) among public laboratory HCWs in Central Peninsular Malaysia. A cross-sectional study was conducted from October to December 2021 with a total of 406 respondents participating in this study. Anxiety symptoms were assessed using the Malay-validated 7-items GAD questionnaire. The cut-off points to define probable GAD were scores of eight and above. A descriptive analysis and multiple logistic regression were conducted to calculate the prevalence of probable GAD and its associated factors. The prevalence of probable GAD among laboratory HCWs was 20.7%. Factors associated with probable GAD among laboratory HCWs during the COVID-19 pandemic were younger age group (aOR=3.23; 95% CI:1.22, 8.57), excessive working time of more than 50 hours per week (aOR=3.09; 95% CI: 1.76, 5.42) and working with COVID-19 specimens (aOR=1.83; 95% CI:1.07, 3.14). HCWs in the national laboratory were at risk of having probable GAD during the COVID-19 pandemic, especially among the younger age group, those exposed to excessive working time and those who handled COVID-19 specimens. Thus, stakeholders should improve the existing psychological support and provide supportive working environments including a regular mental health screening and early intervention among those who were screened positive for probable GAD.